(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The results of constructing a mathematical description of the process of measuring transformation of jet flowmeters for measuring low liquid and gas flow rates are presented. The measurement method is based on determining the value of the flow rate by the force of interaction between the controlled flow, formed into a jet, and a rigid baffle.